2021
DOI: 10.1007/s12668-021-00925-3
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis, Characterization, and Antifungal Activity of Synthesized Silver Nanoparticles (AgNPS) from Garcinia Kola Pulp Extract

Abstract: The prevention or cure of microbial infections are mostly combated with the use of antibiotics. However, the activity of most of the available antibiotics had been nullified by fungi resistance. This study was aimed at the investigation of the antifungal property of silver nanoparticles (AgNPs) synthesized from Garcinia kola pulp. The pulp of Garcinia kola were obtained from its ripe fruit, dried and pulverized into fine particles and extracted with water. The extract was mixed with 1mM aqueous silver nitrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The stability, size, aggregation, and structure of the NPs have all been investigated using ultraviolet analysis [25] . When incident light rays interact with the conduction band electrons on the surface of the metal NPs, each metal oxide and metal NP has a unique absorbance wavelength, which is determined by the UV spectrum [26] . According to Aisida et al, [27] , the UV spectrum's 280 to 450 nm region corresponds to the particular absorbance band for IONPs Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The stability, size, aggregation, and structure of the NPs have all been investigated using ultraviolet analysis [25] . When incident light rays interact with the conduction band electrons on the surface of the metal NPs, each metal oxide and metal NP has a unique absorbance wavelength, which is determined by the UV spectrum [26] . According to Aisida et al, [27] , the UV spectrum's 280 to 450 nm region corresponds to the particular absorbance band for IONPs Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The green technique is preferred since it has a lower impact on toxicity, fewer biological risks, and uses less energy [ 12 ]. The antibacterial [ 13 ], antiviral [ 14 ], antifungal [ 15 ], anti-inflammatory [ 16 ], antiseptic [ 17 ] and anticancer[ 18 ] properties of green synthesised nanoparticles are well established. Among these silver nanoparticles has already been applied in various fields i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Other compounds isolated from the seeds of G. kola includes kolaviron (a bioflavonoid), garcinoic acid, garcinal, benzophenone and kolanone [30]. Synthesis of metallic NPs using extracts of G. kola and its biological activities have also been reported [37,38]. To the best of our knowledge, no anti-cancer study has been reported using G. kola synthesised AuNPs.…”
Section: Introductionmentioning
confidence: 99%